Structural Design and Random Vibration Analysis of a High-Stability Momentum Wheel - Yukuan Xie; Yuan Xue; Hongxiang Wang; Yinjin Sun (Machines)
A novel expandable wheel body assembly is designed in this paper. The wheel body assembly utilizes the elastic deformation of the hub to clamp the bearing assembly. The gaps between them are effectively eliminated by this structure, improving the rotational precision and operational stability of the momentum wheel. A finite element model of the momentum wheel was established, and stress analysis was conducted using finite element analysis (FEA) software ANSYS 2025R1 to validate its mechanical integrity. The results demonstrate that the designed momentum wheel meets the required strength specifications. Additionally, the random vibration characteristics of the momentum wheel in a space environment were analyzed using ANSYS simulations, and a corresponding random vibration test was conducted. The good agreement between simulation and experimental results validates the reliability of the finite element model. The results indicate that this new type of momentum wheel can work reliably in aerospace conditions.